A Systematic Review of the Literature on Health and Wellness Coaching: Defining a Key Behavioral Intervention in Healthcare. Issue 4 (July 2013) - Wolever, Ruth Q.; Simmons, Leigh Ann; Sforzo, Gary A.; Dill, Diana; Kaye, Miranda; Bechard, Elizabeth M.; Southard, Mary Elaine; Kennedy, Mary; Vosloo, Justine; Yang, Nancy
Primary Objective: Review the operational definitions of health and wellness coaching as published in the peer-reviewed medical literature. Background: As global rates of preventable chronic diseases have reached epidemic proportions, there has been an increased focus on strategies to improve health behaviors and associated outcomes. One such strategy, health and wellness coaching, has been inconsistently defined and shown mixed results. Methods: A Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)—guided systematic review of the medical literature on health and wellness coaching allowed for compilation of data on specific features of the coaching interventions and background and training of coaches. Results: Eight hundred abstracts were initially identified through PubMed, with 284 full-text articles ultimately included. The majority (76%) were empirical articles. The literature operationalized health and wellness coaching as a process that is fully or partially patient-centered (86% of articles), included patient-determined goals (71%), incorporated self-discovery and active learning processes (63%) (vs more passive receipt of advice), encouraged accountability for behaviors (86%), and provided some type of education to patients along with using coaching processes (91%). Additionally, 78% of articles indicated that the coaching occurs in the context of a consistent, ongoing relationship with a human coach who is trained in specific behavior change, communication, and motivational skills. Conclusions: Despite disparities in how health and wellness coaching have been operationalized previously, this systematic review observes an emerging consensus in what is referred to as health and wellness coaching; namely, a patient-centered process that is based upon behavior change theory and is delivered by health professionals with diverse backgrounds. The actual coaching process entails goal-setting determined by the patient, encourages self-discovery in addition to content education, and incorporates mechanisms for developing accountability in health behaviors. With a clear definition for health and wellness coaching, robust research can more accurately assess the effectiveness of the approach in bringing about changes in health behaviors, health outcomes and associated costs that are targeted to reduce the global burden of chronic disease.